The Role of Dynamic Capabilities in Moderating the Influence of Entrepreneurial Alertness and Entrepreneurial Intuition on Business Opportunity Recognition in the Café Industry - Widjojo Suprapto; Sherly Agustine; Dhyah Harjanti; Maria Praptiningsih (Master of Management, School of Business and Management, Petra Christian University, 2024)
The aim of this study is to examine the influence of alertness and intuition among entrepreneurs on recognizing business opportunities in the café industry, with dynamic capabilities as the moderating variable. Although the pandemic of COVID-19 has become a distant history, many business owners are still struggling to find new grounds in the new business landscape which is dominated by the uprising of e-commerce and unconventional business platforms. So, many of them have started to venture into new opportunities to expand their business interests, and café business offers a new option, especially in rural areas where people are killing their time by socializing with others in warung (food stalls). Because the study is seeking explanations on how dynamic capabilities affects the relationship between independent variables and dependent variable, the research method is adopting the quantitative research method, in which the data are collected using questionnaires from purposely selected respondents. For this study, the questionnaires were distributed to small business owners in some rural areas or small cities, and a hundred valid questionnaires were obtained and processed with smartPLS to get the robustness of the study and the results of the hypothesis tests. The results show that entrepreneurial alertness has a significant influence on business opportunity recognition, but entrepreneurial intuition does not have any influence on business opportunity recognition among café business owners in rural areas. Dynamic capabilities do not show any moderating effect between entrepreneurial alertness and business opportunity recognition, however, dynamic capabilities show the moderating effect on entrepreneurial intuition and business opportunity recognition.